2011
DOI: 10.1165/rcmb.2010-0140oc
|View full text |Cite
|
Sign up to set email alerts
|

Notch Induces Myofibroblast Differentiation of Alveolar Epithelial Cells via Transforming Growth Factor- -Smad3 Pathway

Abstract: Notch is an ancient cell-signaling system that regulates the specification of cell fate. This study examined the role of Notch in the epithelial-mesenchymal transition (EMT) and myofibroblast differentiation of cultured RLE-6TN cells (i.e., rat alveolar epithelial cells). The activation of Notch, either by ectopic expression of the Notch intracellular domain or by the co-culture of RLE-6TN cells with L-Jagged1 cells, induces the expression of smooth muscle α-actin (SMA) and other mesenchymal marker genes (coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 42 publications
2
45
0
5
Order By: Relevance
“…Downregulation of TGF-β1 expression and modulation of TGF-β/Smad signaling may be effective in preventing organ fibrosis [24]. Investigators have previously demonstrated that TGF-β1 overexpression has been associated with enhanced myofibroblast differentiaon [25,26]. In our data it was observed that the expressions of TGF-β1 and p-Smad2/3 were markedly decreased in cultured CFs under LH treatment.…”
Section: Discussionsupporting
confidence: 56%
“…Downregulation of TGF-β1 expression and modulation of TGF-β/Smad signaling may be effective in preventing organ fibrosis [24]. Investigators have previously demonstrated that TGF-β1 overexpression has been associated with enhanced myofibroblast differentiaon [25,26]. In our data it was observed that the expressions of TGF-β1 and p-Smad2/3 were markedly decreased in cultured CFs under LH treatment.…”
Section: Discussionsupporting
confidence: 56%
“…Some collagen-producing myofibroblasts contain S100A4 (fibroblast-specific protein 1, calvasculin), a prototypical marker for EMT (24) (Figure 4C). Codetection of FAP, a protease selectively induced in fibrotic foci (25), together with Notch ( Figure 4D) or b-catenin ( Figure 4E), two critical signaling proteins that control the EMT phenotype (26,27), as well as the observed induction of Snail 1 Slug transcription factor ( Figure 4F), suggest that EMT may play a role in lung fibrogenesis in our model.…”
Section: Proliferative Phasementioning
confidence: 78%
“…Genome-wide transcriptome studies in healthy or mutated T-cells (Chadwick et al, 2009;Dohda et al, 2007;Palomero et al, 2006;Weerkamp et al, 2006), mouse embryonic stem (ES) cells (Main et al, 2010;Meier-Stiegen et al, 2010), alveolar epithelial cells (Aoyagi-Ikeda et al, 2011), endometrial stromal cells (Mikhailik et al, 2009), C2C12 mouse myoblast cells (Buas et al, 2009) and Drosophila myogenic cells (Krejci et al, 2009) have unraveled distinct sets of Notch target genes with rather limited overlap of the transcriptomes. This is the case even when comparing transcriptome studies that were carried out with relatively similar modes and durations of Notch induction (summarized in Fig.…”
Section: Reviewmentioning
confidence: 99%